Improving the TFold test for differential shotgun proteomics - Carvalho, Paulo C. (Oxford University Press, 2012)
Summary: We present an updated version of the TFold software for pinpointing differentially expressed proteins in shotgun proteomics experiments. Given an FDR bound, the updated approach uses a theoretical FDR estimator to maximize the number of identifications that satisfy both a fold-change cutoff that varies with the t-test P-value as a power law and a stringency criterion that aims to detect lowly abundant proteins. The new version has yielded significant improvements in sensitivity over the previous one. Availability: Freely available for academic use at http://pcarvalho.com/patternlab. Contact: paulo@pcarvalho.com